2018
DOI: 10.1016/j.trci.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of apolipoprotein E genotypes on vitamin E and memantine treatment outcomes in Alzheimer's disease

Abstract: IntroductionBecause apolipoprotein E (APOE) genotypes are known risk factors for Alzheimer's disease (AD), they have been measured in clinical trial participants to determine their effect on treatment outcome.MethodsWe determined APOE genotypes in a subset of subjects (N = 415) who participated in a randomized controlled trial of vitamin E and memantine in 613 veterans with mild-to-moderate AD.ResultsSimilar to the primary study, substudy participants receiving vitamin E also had slower functional decline than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous research has shown a significant interaction between APOE genotype on AD progression with ε4 carriers declining faster than non-carriers following vitamin E and memantine treatment [49]. Possible mechanisms are that APOE may influence AD risk though its role in cholesterol transport, one consideration is that vitamin E and cholesterol share mechanisms of delivery to cells via LDL particles that genotype might influence [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a significant interaction between APOE genotype on AD progression with ε4 carriers declining faster than non-carriers following vitamin E and memantine treatment [49]. Possible mechanisms are that APOE may influence AD risk though its role in cholesterol transport, one consideration is that vitamin E and cholesterol share mechanisms of delivery to cells via LDL particles that genotype might influence [18].…”
Section: Discussionmentioning
confidence: 99%
“…The apolipoprotein E(APOE) genotype is a known risk factor for AD. Vitamin E administration may help delay cognitive decline by modulating the response to treatment in APOE genotypes ( Belitskaya-Lévy et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nutrients like omega-3, omega-6, PUFA, and MUFA found in nuts, and fish can play most roles in the clearance of Aβ, increase Aβ [ 75 ], phagocytosis [ 76 ], improve behavioral motor function and survival, expression to tau [ 79 ], reduce microglia activities [ 80 ]. vitamin D inhibits induced fibrillar Aβ apoptosis [ 77 ], and vitamin E, APOe4 carrier declined faster with vitamin E association [ 74 ]. EPA and DHA increase the non-amyloidogenic processing of APP [ 78 ].…”
Section: Resultsmentioning
confidence: 99%